Psychological Support of Sayyidah Khadijah (Ra) in The Early Reception of Revelatio - Ernaeny, Windy; Agus Nurhadi; Aptaarkhan Aurell Is Haque (Psikis : Jurnal Psikologi Islami, 2025)
Psychological support in a marriage between husband and wife is an essential factor that determines the sustainability and quality of the relationship. It is both a responsibility and a blessing from Allah SWT. The relationship between the Prophet Muhammad SAW and Sayyidah Khadijah (RA) exemplifies psychological support within the household. Sayyidah Khadijah (RA)'s presence provided the emotional stability that the Prophet Muhammad SAW needed, particularly during the early period when he received revelations from Allah through the Angel Jibril in the Cave of Hira. The Prophet Muhammad SAW received the revelation with the support of Sayyidah Khadijah (RA), despite not having prepared himself for the role of the Messenger of Allah SWT who would profoundly transform humanity. This study employs a descriptive qualitative method, aiming to explore in depth the psychological support offered by Sayyidah Khadijah RA to the Prophet Muhammad SAW during the initial phase of revelation. The data were collected through a literature review of historical texts, narrations (riwayat), and relevant Quranic exegeses (tafsir). The study concludes that the psychological support provided by Sayyidah Khadijah RA was multidimensional — it offered encouragement, emotional protection, and strengthened the Prophet’s belief in his divine mission. Their relationship illustrates that psychological support is a vital element in nurturing purpose and determination, ultimately contributing to monumental achievements in the history of religion.